2019
DOI: 10.1039/c9dt01922g
|View full text |Cite
|
Sign up to set email alerts
|

Copper(ii) complexes with 2,2′:6′,2′′-terpyridine, 2,6-di(thiazol-2-yl)pyridine and 2,6-di(pyrazin-2-yl)pyridine substituted with quinolines. Synthesis, structure, antiproliferative activity, and catalytic activity in the oxidation of alkanes and alcohols with peroxides

Abstract: The toxicity of six new Cu(ii) complexes was evaluated in cancer derived cell lines. A model of competitive interaction of hydroxyl radicals with CH3CN and RH in the catalyst cavity has been proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 136 publications
3
28
0
Order By: Relevance
“…The Cu(II) complexes of various terpyridines, equipped in 4′‐position with heteroaromatic rings, were utilized in the anaerobic oxidation of alkanes and secondary alcohols using H 2 O 2 and tert ‐butyl hydroperoxide (TBHP), as the respective oxidants . The oxidation of alkanes yields hydroperoxides as the primary products, which were – after reduction with PPh 3 – quantified by gas‐chromatographic analysis.…”
Section: Terpyridine Complexes As Catalysts For Organic Reactionsmentioning
confidence: 99%
“…The Cu(II) complexes of various terpyridines, equipped in 4′‐position with heteroaromatic rings, were utilized in the anaerobic oxidation of alkanes and secondary alcohols using H 2 O 2 and tert ‐butyl hydroperoxide (TBHP), as the respective oxidants . The oxidation of alkanes yields hydroperoxides as the primary products, which were – after reduction with PPh 3 – quantified by gas‐chromatographic analysis.…”
Section: Terpyridine Complexes As Catalysts For Organic Reactionsmentioning
confidence: 99%
“…Substituted terpyridines such as 4 0 -chloro-2,2 0 :6 0 ,2 00 -terpyridine continue to be recognized as useful chelating ligands for many transition-metal ions, including platinum(II) (Qin et al, 2019), copper(II) (Choroba et al, 2019), cadmium(II) (Li et al, 2020), and zinc(II) (Li et al, 2019). Metal complexes containing zinc(II) and substituted terpyridines as chelating ligand have been shown to have promising antitumor activity (Liang et al, 2019).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Machura et al [79] described the oxidation of inert alkanes to alkyl hydroperoxides by H2O2 catalyzed with monomeric oxovanadium(V) complexes of 8-hydroxyquinoline derivatives as noninnocent ligands (Scheme 4). The analogous ligands in complexes with copper or rhenium were used in oxidations by peroxides [80][81][82][83] Gushchin, Kuznetsov, et al recently [84,85] observed high activity among the vanadium complexes shown in Scheme 5 in the oxidation of hydrocarbons with peroxides. The mechanism for the generation of OH radicals is presented in Scheme 6.…”
Section: Oxidation Of Hydrocarbons and Alcohols With Peroxides Catalymentioning
confidence: 99%
“…Machura et al [79] described the oxidation of inert alkanes to alkyl hydroperoxides by H2O2 catalyzed with monomeric oxovanadium(V) complexes of 8-hydroxyquinoline derivatives as noninnocent ligands (Scheme 4). The analogous ligands in complexes with copper or rhenium were used in oxidations by peroxides [80][81][82][83] Scheme 4. Cleavage of the HO-OH bond and intramolecular electron transfer in a vanadium complex in the absence of PCA.…”
Section: Oxidation Of Hydrocarbons and Alcohols With Peroxides Catalymentioning
confidence: 99%